2012
DOI: 10.1371/journal.pone.0032533
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Estimating GFR and Treatment Effect in ADPKD Patients: Results and Implications of a Longitudinal Cohort Study

Abstract: Trials failed to demonstrate protective effects of investigational treatments on glomerular filtration rate (GFR) reduction in Autosomal Dominant Polycystic Kidney Disease (ADPKD). To assess whether above findings were explained by unreliable GFR estimates, in this academic study we compared GFR values centrally measured by iohexol plasma clearance with corresponding values estimated by Chronic Kidney Disease Epidemiology Collaboration (CKD-Epi) and abbreviated Modification of Diet in Renal Disease (aMDRD) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 41 publications
0
35
0
1
Order By: Relevance
“…A core study primarily aimed to assess whether 12-month treatment with sirolimus added on to conventional treatment significantly reduced measured GFR decline (12,13) versus conventional treatment alone and was safe. Evidence that sirolimus may safely slow GFR decline would have provided the background for an extension phase to evaluate treatment effect on kidney and cystic growth and progression to ESRD over an additional 2-year follow-up.…”
Section: Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…A core study primarily aimed to assess whether 12-month treatment with sirolimus added on to conventional treatment significantly reduced measured GFR decline (12,13) versus conventional treatment alone and was safe. Evidence that sirolimus may safely slow GFR decline would have provided the background for an extension phase to evaluate treatment effect on kidney and cystic growth and progression to ESRD over an additional 2-year follow-up.…”
Section: Objectivesmentioning
confidence: 99%
“…GFR was measured every 6 months by iohexol plasma clearance (12,13). Computed tomography images were acquired and analyzed at baseline and 12 months as previously reported (15,16) (Supplemental Appendix 2).…”
Section: Randomization Allocation Concealment and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the oxidant-antioxidant balance was likely reliably reflected by ADMA. Because it has been reported that prediction formulas unreliably estimate actual GFR values and fail to detect their changes over time in ADPKD, another possible limitation of this study is the method that used eGFR instead of direct kidney measurements [48]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the ALADIN trial, the clinically relevant renoprotective effect of Octreotide-LAR would have been missed if GFR had not been measured, but just estimated with equations. In the same vein, the prediction formulas CKD Epidemiology Collaboration and aMDRD unreliably estimated actual GFR values, and failed to predict GFR changes over time in a cohort of adult patients with ADPKD, independent of their kidney function [29] . Similarly, evidence is available that questions the use of any GFR estimation formula to monitor renal disease progression and response to treatment in type 2 diabetics with normo-or microalbuminuria [30] .…”
Section: Unreliable Assessment Of Renal Functionmentioning
confidence: 99%